2006
DOI: 10.2106/jbjs.e.00851
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Total Shoulder Arthroplasty

Abstract: Our findings indicate that the reverse total prosthesis should be reserved for the treatment of very disabling shoulder arthropathy with a massive rotator cuff rupture, and it should be used exclusively in patients over seventy years old with low functional demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(174 citation statements)
references
References 19 publications
7
162
1
4
Order By: Relevance
“…Woodruff et al [25] reported on 13 shoulders with a postoperative score of 59 after a mean followup of 87 months. However, our scores are slightly inferior to some that have been reported in patients with cuff tear arthropathy with Constant-Murley scores of up to 60 to 65 (Table 2) [4,7,11,18,20,[22][23][24].…”
Section: Figcontrasting
confidence: 81%
See 1 more Smart Citation
“…Woodruff et al [25] reported on 13 shoulders with a postoperative score of 59 after a mean followup of 87 months. However, our scores are slightly inferior to some that have been reported in patients with cuff tear arthropathy with Constant-Murley scores of up to 60 to 65 (Table 2) [4,7,11,18,20,[22][23][24].…”
Section: Figcontrasting
confidence: 81%
“…However, the mean followup was only 56 months and further studies are needed to determine long-term survival of the implant in this patient group. Age must therefore be taken into consideration when considering a reverse arthroplasty [11]. If an elderly patient with rheumatoid arthritis has pain and poor active ROM (pseudoparalysis) as a result of arthritic changes and a massive cuff tear, a reverse arthroplasty should be considered.…”
Section: Figmentioning
confidence: 99%
“…Improvement of over 40% for both the relative Constant Score and SSV after a mean follow-up of 93 months is consistent with other studies of RTSA in older patients. 18 Favard et al (2011) postulated that this may reflect the delayed consequences of radiographic signs of potential failure, however this has not been confirmed. 9 In our study, we found no significant change in both the functional scores and SSV over a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…This large database study does not have preoperative and postoperative patient outcome scores. However, the clinical improvement after RTSA and TSA has been widely documented 3,[18][19][20] and was not the aim of this study.…”
Section: Original Research and Contributionsmentioning
confidence: 99%